Rescue of CAMDI deletion‐induced delayed radial migration and psychiatric behaviors by HDAC6 inhibitor - Fukuda, Toshifumi (EMBO Rep, 2016)
The DISC1‐interacting protein CAMDI has been suggested to promote radial migration through centrosome regulation. However, its physiological relevance is unclear. Here, we report the generation and characterization of CAMDI‐deficient mice. CAMDI‐deficient mice exhibit delayed radial migration with aberrant neural circuit formation and psychiatric behaviors including hyperactivity, repetitive behavior, and social abnormality typically observed in autism spectrum disorder patients. Analyses of direct targets of CAMDI identify HDAC6 whose α‐tubulin deacetylase activity is inhibited by CAMDI at the centrosome. CAMDI deficiency increases HDAC6 activity, leading to unstable centrosomes with reduced γ‐tubulin and acetylated α‐tubulin levels. Most importantly, psychiatric behaviors as well as delayed migration are significantly rescued by treatment with Tubastatin A, a specific inhibitor of HDAC6. Our findings indicate that HDAC6 hyperactivation by CAMDI deletion causes psychiatric behaviors, at least in part, through delayed radial migration due to impaired centrosomes.